How would you rewrite the following equation into the Euler's (not improved) method? y'= y -x - 1, y(0) this is what I attempted: Ysub(n+1) = Ysub (n)+ h (-x sub (n), Ysub (n) - 1) Is this correct?
Follow Math Help Forum on Facebook and Google+
Originally Posted by googoogaga How would you rewrite the following equation into the Euler's (not improved) method? y'= y -x - 1, y(0) this is what I attempted: Ysub(n+1) = Ysub (n)+ h (-x sub (n), Ysub (n) - 1) Is this correct? $\displaystyle Y_{n+1} = Y_{n}+ h (Y_n-x_n - 1) $
View Tag Cloud